Relative consumption concerns or non-monotonic preferences? - Inga Hillesheim; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
We conduct a classroom survey to investigate the willingness to sacrifice consumption in absolute terms in order to ascend above others in terms of consumption levels. In contrast to other studies using survey methodologies, participants are divided into a treatment and a control group. This allows us to distinguish whether choosing less in absolute terms is really induced by relative consumption concerns, or else by nonmonotonic preferences. We find that relative consumption concerns provide a good explanation for choosing less in the case of some goods, while this is not the case for a number of other goods.
Keywords: C91; D63; D10; 330; status consumption; social status; behavioral economics; other-regarding preferences; Konsuminterdependenz; Präferenztheorie; Verhaltensökonomik; Theorie